If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4(3x + -8) + -2(x + 6) = x + -9 Reorder the terms: 5 + 4(-8 + 3x) + -2(x + 6) = x + -9 5 + (-8 * 4 + 3x * 4) + -2(x + 6) = x + -9 5 + (-32 + 12x) + -2(x + 6) = x + -9 Reorder the terms: 5 + -32 + 12x + -2(6 + x) = x + -9 5 + -32 + 12x + (6 * -2 + x * -2) = x + -9 5 + -32 + 12x + (-12 + -2x) = x + -9 Reorder the terms: 5 + -32 + -12 + 12x + -2x = x + -9 Combine like terms: 5 + -32 = -27 -27 + -12 + 12x + -2x = x + -9 Combine like terms: -27 + -12 = -39 -39 + 12x + -2x = x + -9 Combine like terms: 12x + -2x = 10x -39 + 10x = x + -9 Reorder the terms: -39 + 10x = -9 + x Solving -39 + 10x = -9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -39 + 10x + -1x = -9 + x + -1x Combine like terms: 10x + -1x = 9x -39 + 9x = -9 + x + -1x Combine like terms: x + -1x = 0 -39 + 9x = -9 + 0 -39 + 9x = -9 Add '39' to each side of the equation. -39 + 39 + 9x = -9 + 39 Combine like terms: -39 + 39 = 0 0 + 9x = -9 + 39 9x = -9 + 39 Combine like terms: -9 + 39 = 30 9x = 30 Divide each side by '9'. x = 3.333333333 Simplifying x = 3.333333333
| 8n+22=-2(-4n+3)+7n | | r+8.4=-0.5 | | 6=-3(r+2) | | w^2+2w=99 | | 4a=a-18 | | 2=2x-6 | | -3n+30=-6(6+6n) | | 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) | | (-8y-5)(7y)*y=-3 | | 5p+2=11+4p | | 57=-7(7b-3)-(7-6b) | | 6x+6=3x | | 26-5x=-7-3r | | 4(u-4)-6u=4 | | 20-4(2w+1)=6w-4(6+w) | | (-8y-5)(7y)y=-3 | | 8c-3d=6 | | 1d+8=2d-17 | | 0.7m+0.3m=2m-4 | | p=m+k+n | | -6(x-3)-4(6-6x)=12 | | -6-3(6+4x)=-24-2x | | 91=-7(2n-7) | | -5*(1/9+x)=0 | | 114=(x+2)15-3x |